Gingival Index as a Marker of Oral Inflammation in Systemic Lupus Erythematosus - Risya Cilmiaty; Widia Susanti; Betty Saptiwi; Adi Prayitno; Alfiyah Pujiyati; Damiana Tribhuwaneswari Mahendra Wardhani (Jurnal Kesehatan Gigi, 2026)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder with multisystem involvement that can affect periodontal tissues, leading to gingival inflammation. While global studies have employed various clinical parameters to assess this association, specific research comparing gingival inflammation between SLE patients and healthy controls in the Indonesian population remains limited. This study aimed to investigate this association by using the Gingival Index (GI) in a cohort from Surakarta, Indonesia. This comparative analytical study involved 100 participants (50 SLE patients and 50 healthy controls). SLE diagnosis was confirmed using the 2019 EULAR/ACR criteria. Gingival inflammation was assessed with the Löe and Silness Gingival Index. The Mann-Whitney U test was used to compare GI scores between groups, and Spearman's correlation was used to analyze the relationship between GI and group status, with statistical significance set at p < 0.05. The SLE group exhibited a significantly higher median GI of 0.5 (IQR: 0.0–1.0) compared to 0.1 (IQR: 0.0–0.2) in the healthy control group (p < 0.05). Spearman's correlation confirmed a moderate association between group status and GI scores (r = -0.379, p < 0.05), indicating that the SLE group had higher gingival inflammation compared to healthy controls. These findings indicate that SLE is significantly associated with increased gingival inflammation, highlighting the interplay between systemic autoimmunity and periodontal health. The Gingival Index may serve as a useful clinical marker for systemic inflammation in SLE, which underscores the need for collaborative care between rheumatologists and dental professionals. Keyword: systemic lupus erythematosus (SLE); gingival index (GI); periodontal health; gingival inflammation; autoimmune disease